Incidencia de la aplicación de estrategias metodológicas en el proceso de enseñanza aprendizaje de la prelectura a través de cuentos pictográficos en primer año educación básica – preparatoria en la escuela de educación básica Lic. Jaime Andrade Fabara ubicada en la parroquia Eloy Alfaro, en la provincia de Cotopaxi, del cantón Latacunga. - Ortega Moreno, Erika Alexandra (2020)
The present research project has identified the incidence of the application of methodological strategies in the teaching-learning process of pre-reading, through pictographic stories in the first year of basic education (preparatory) at Eschol de Education Básica "Lic. Jaime Andrade Fabara". Teachers, parents, and especially children who are seen as the present to change the future because they are in a development process and recognition of their abilities and skills will use the same research. Hence, it is aimed at the youngest to strengthen and motivate prereading from an early age. In the research development, relevant data was found, which shows that the Ecuadorian population is not a reader, and that is why this project was framed, in the objective of improving the processes of teaching-learning in pre-reading. In this research, the descriptive method was used based on the most relevant existing theories for the benefit of the community, and especially early childhood education, starting from previous knowledge to reach their potential development, and that is why the approach is used quantitatively because it admits valuing based on data and qualitative, allowed to identify its weaknesses and strengths, which led to understanding the importance of the development of the project. To stimulate the language and start with the pre-reading process, through methodological strategies. This will allow us to improve language, creativity, imagination, and visual discrimination. Through, pictographic stories, which are framed in the researchers' own creation, mainly based on areas, objectives, and skills of the initial education curriculum. The purpose of this educational resource is for children to begin to recognize phonemes and graphemes, which are the most important for the beginning of the reading.